Área de proteção ambiental Alter do Chão: georreferenciamento dos conflitos socioambientais - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The Alter do Chão Environmental Protection Area is a region where there are many socio-environmental conflicts. Even before the creation of the APA Alter do Chão, carried out by Law nº 17.771/03 of June 2, 2003, some of these conflicts already occurred. Most of these occur due to lack of regulation, considering that the National System of Conservation Units (SNUC) establishes a period of five years for the preparation of the Master Plan for Environmental Management, as well as the municipal legislation itself requires a Master Plan. However, after 18 years, the City Hall still hasn't implemented it, which brings legal uncertainty to entrepreneurs and makes the environmental organization of the territory unfeasible by community members. The objective of this research is the mapping of socio-environmental conflicts in the APA Alter do Chão, located in the municipality of Santarém/PA, using georeferencing as a way of mapping the conflicting areas. The materials and approach methods consisted of geoprocessing techniques and analysis of satellite images with the main actors involved in the conflicts, in addition to field research, in order to outline the profile of the area in question. Several socio-environmental conflicts were identified, some due to the fact that the actors involved did not know the nature and attributions of an APA, as well as those that originate from the interests of companies, the market, tourism, among others, which end up generating conflicts. The results achieved by the research can be used as elements for understanding the existing socio-environmental conflicts in the APA, aiming at effective actions for the sustainable use of its natural and territorial resources and in the mitigation of existing conflicts.
Keywords: Área protegida; Unidade de conservação; Georreferenciamento; Alter do Chão; CNPQ::CIÊNCIAS HUMANAS